Syndromic obesity and diabetes: changes in body composition with age and mutation analysis of ALMS1 in 12 United Kingdom kindreds with Alstrom syndrome. - Minton, J; Owen, K; Ricketts, C; Crabtree, N; Shaikh, G; Ehtisham, S; Porter, JR; Carey, C; Hodge, D; Paisey, R; Walker, M; Barrett, T (2006)
CONTEXT: Alström syndrome (AS) is a monogenic form of infancy-onset obesity and insulin resistance, caused by ALMS1 mutations. The natural history of the insulin resistance is unknown, in particular how this relates to changes in body composition. It is also unclear how ALMS1 mutations relate to the characteristic phenotype. OBJECTIVES: Our objectives were to characterize body composition and metabolic parameters, to establish ALMS1 mutation spectrum of United Kingdom AS patients, and to determine whether a genotype-phenotype correlation exists. DESIGN AND PATIENTS: We conducted a cross-sectional cohort study of 12 unrelated subjects with AS. Age-standardized body composition was assessed by anthropometry and dual-energy x-ray absorptiometry and insulin sensitivity by homeostasis model assessment. The exons and intron-exon boundaries of ALMS1 were directly sequenced. SETTING: The study was performed during the annual Alström Syndrome UK multidisciplinary screening clinic. RESULTS: AS patients have early-onset obesity, but body mass index, waist circumference, and body fat from dual-energy x-ray absorptiometry were negatively correlated with age (r = -0.37, P = 0.2; r = -0.84, P = 0.002; and r = -0.6, P = 0.05). Despite this, insulin resistance increased, demonstrated by raised fasting insulin and fall in homeostasis model assessment insulin sensitivity with age (r = -0.64, P = 0.02). ALMS1 mutations were identified in 10 of 12 patients, with a potential founder mutation in exon 16 present in five [np 10775del (C); Del3592fs/ter3597]. No genotype-phenotype correlation was observed. CONCLUSIONS: We identified mutations in ALMS1 in more than 80% of patients with no genotype-phenotype correlation. In AS, severe childhood obesity, waist circumference, and body fat decrease with age, whereas insulin resistance increases. The abdominal obesity, insulin resistance, diabetes, hypertriglyceridemia, and hypertension suggest that AS could represent a monogenic model for the metabolic syndrome.